Quantitative analysis of oncostatin M levels in chronic periodontitis patients - Farooque Khan; Surekha Rathod; Abhay Kolte; Madhur Gupta; Suresh Chari; Noopur Gonde (Wolters Kluwer Medknow Publications, 2020)
Background: Oncostatin M (OSM) is the cytokine from the family of interleukin-6. Inflammation, tissue turnover, healing, and repair alter the levels of OSM. The present study was aimed to evaluate the gingival crevicular fluid (GCF) and serum OSM levels in clinically healthy, chronic gingivitis and chronic periodontitis (CP) patients and subsequently after nonsurgical periodontal therapy (NSPT). Materials and Methods: Sixty patients were equally divided into four groups as healthy, chronic gingivitis, CP, and CP with NSPT were included in this study. After 6 weeks of initial periodontal therapy the clinical parameters were measured and OSM levels in GCF and serum were assessed by using enzyme linked immunosorbent assay. Results: The levels of OSM in GCF and serum increased significantly with severity of periodontal disease. There was a significant decrease in OSM levels in GCF and serum in CP with NSPT group. Conclusion: GCF and serum OSM levels can be considered as an appropriate biomarker to be correlated with the severity of periodontal disease. Thus, the increased OSM levels suggest its role in the pathogenesis of periodontal disease and prevent systemic complications.